Flow over rectangular cylinder: Effects of cylinder aspect ratio and Reynolds number. (1st April 2021) - Mashhadi, A.; Sohankar, A.; Alam, Md. Mahbub
Highlights: Flow over rectangular cylinders are conducted at Re = 30 – 200 and AR = 0.25 – 4. We examined AR and Re influence on the flow structure and aerodynamic parameters. The critical Re associated with the onset of vortex shedding linearly increase with AR . Two distinct mechanisms of the separation bubble formation are imparted. Abstract: Numerical simulations of two- and three-dimensional unconfined flows over rectangular cylinders are conducted at Reynolds number Re = 30 – 200. The cylinder cross-sectional aspect ratio AR (length-to-width) is varied as 0.25, 0.5, 1.0, 2.0, 3.0 and 4.0. The focus is given on how AR and Re influence the flow structure and associated aerodynamic parameters. The first critical Reynolds number ( Recr1 ) associated with the transition from the steady flow to the two-dimensional unsteady flow is determined for each AR and found to linearly increase with increasing AR . The same observation is made for the second critical Reynolds number ( Recr2 ) where the two-dimensional unsteady flow metamorphoses into the three-dimensional unsteady flow. A larger Re is required for a larger AR to have the onset of vortex shedding or the transition from two-dimensional flow to the three-dimensional. Three distinct scenarios of the flow separation and reattachment are identified in the ranges of Re and AR examined. The physical insight into the flow dependence on AR and Re is provided. Both AR and Re play a role in the formation of separation bubbles on the cylinder side surfaces. Two distinct mechanisms of the separation bubble formation are imparted. The detailed flow structures are linked to the mean and fluctuating forces and Strouhal numbers. The vortex strength beefs up with increasing Re but diminishes with AR, as do the normal and shear stresses and fluctuating forces. Graphical abstract: Image, graphical abstract